Revealing The Meaning Of Bai ’And Tijarah In Al-Qur'an (Interpretation Of Economic Verses) - Farid Ikhwanuddin; Roni Hidayat (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2019)
One form of economic activity carried out by humans is trade. It can be said that trade is the oldest activity carried out by humans in fulfilling their daily needs. Mecca at that time was a major international trade and shopping center, and Islam was born in the militia of Mecca trade. Once the Islamic attachment to trading activities, many narratives of the verses of the Qur'an seemed to be directed at the merchants. Qur'an was first addressed to the merchants reflected in the language and ideas